Valorização do trabalho docente no plano de cargos e carreira de Uberlândia: a perspectiva dos profissionais da rede municipal de ensino - Pereira, Mariane Gomes (2017)
Our dissertation is a research aiming at investigating and understanding the valorization of the teaching work, from the Career and Job Plans from Uberlândia, Minas Gerais, from the perspective of teachers, regarding continuous training, payment, career and working conditions. To reach this goal objective, we carried out a bibliographic survey of dissertations and theses from the Brazilian Digital Library of Theses and Dissertations, from the Brazilian Institute of Information in Science and Technology, used research from scholars in the area, as well as the analysis of educational policies, such as programs and legislation, which directly affect teaching work professional valorization. We focused on the Municipal Career and Job Plans with the objective of comparing them based on the central categories of the research, such as continuous training, payment, career and working conditions. We also carried out a theoretical background understanding on the issues that involve the object of the study about work in capitalist society and its repercussion on teaching work. At another moment, 64 questionnaires were applied to teachers of the municipal school system. To complete the data collected, we conducted interviews with subjects who were involved in the construction of the 2014 Career and Job Plan. By conducting this study, we realize that in the theoretical field there are several discussions on the valorization of the teaching work contemplated in the current policies and programs, by means of proposals of decent payment, adequate workload and offer of programs of initial and continuous training. However, empirical studies have pointed to fragmented actions that do not have a direct impact on working conditions and teaching career. These actions indicate lack of initial and continuous training, low attractiveness of the teaching career, low salaries and lack of adequate working conditions. According to the reality investigated in this study, from the perspective of the teachers from Uberlândia municipal school network, we noticed that there are advances and setbacks, since the continuous training, in the way it has been organized, has allowed the teaching career valorization; the career was designed to favor the development of professionals and the institution and gradually brings results, but it is necessary to implement it in order to achieve valorization of the teaching work; and that the working hours have been little changed, but also allow to value this professional. The payment presents some setbacks, making the devaluation of the teaching work worse and the working conditions are little treated in the Career and Job Plans. Teachers experience the precariousness of their work, which results in the devaluation of the teaching career.